Catalytic Diverse Radical-Mediated 1,2-Cyanofunctionalization of Unactivated Alkenes via Synergistic Remote Cyano Migration and Protected Strategies - Wang, Na; Li, Lei; Li, Zhong-Liang; Yang, Ning-Yuan; Guo, Zhen; Zhang, Hong-Xia; Liu, Xin-Yuan (Organic letters, 2016)
A catalytic radical protocol for 1,2-cyanofunctionalization of unactivated alkenes involving remote cyano migration triggered by addition of diverse carbon- and heteroatom-centered radicals to alkenes has been developed. This powerful strategy provides a diverse platform for the collection of a variety of synthetically important β-functionalized alkyl nitriles bearing densely functionalized carbonyl, cyano, and other various functional groups within the same molecules. The substrates TMS (trimethylsilyl)-protected alkenyl cyanohydrins are straightforwardly accessible via simple cyanosilylation of the corresponding ketones.